Plan de Marketing para la Estética Dental Blanco, de la Ciudad de Loja - Ortega Villamagua, Marco Edison (2017)
The present proposal entitled "MARKETING PLAN FOR THE WHITE DENTAL AESTHETICS OF THE CITY OF SHOP", is oriented to propose strategies based on the internal and external analysis in which the Aesthetic is developed. For this, a survey was carried out on a representative sample of 305 customer surveys. In addition, an interview was conducted with the owner of Aesthetics with the purpose of gathering first hand the information that allows to know the development in the area of marketing of Aesthetics; And a survey was also conducted on the four workers of the company. Among the most outstanding results of the market study are:  87.46% of clients who have aesthetics, have been referred by their friends or co-workers.  The services offered by aesthetics cover the expectations of users (98.21%).  99.51% of aesthetics clients have no justification whatsoever To stop being clients of the Aesthetic Dental White  100% of the clients of Aesthetic Dental BLANCO, mentions that it would recommend to their friends and co-workers to make use of the services offered by aesthetics.  49.85% of the clients of Aesthetic Dental Blanco prefer La Hora as a means of communication. 6  80.30% of users of Aesthetic White Dental prefer to pay for dental services in cash.  The owner of aesthetics implements the administrative process of organization, planning, direction and control of the activities demanded by the company.  Aesthetics complies with the requirements of the Ministry of Labor Relations to ensure all employees of the company and prevent occupational and occupational diseases.  Aesthetics has 100% of professionals with academic preparation according to the activity they perform in the company. Based on the results obtained, the marketing plan is proposed, whose main purpose is to get more customers through mainly focusing, with the help of professionals in the area of graphic design, through La Hora newspaper continue the campaign of advertising. This is supported by the design of a website and a training plan in personal development and service and customer service. This plan also suggests strategic alliances with educational institutions to promote painting contests on the prevention of oral diseases and the correct brushing of teeth. Where you plan to hire pampering to indicate the correct way to brush your teeth using a glass with water instead of keeping the key open and proper use of dental floss. The marketing plan, begins with the formulation of the philosophy to be preached and practiced by BLANCO Dental Aesthetics is how the mission, vision and values are written. Next, the objectives of the marketing plan are set out. For 7 this, the situational analysis of aesthetics begins. The internal analysis of the aesthetics allowed to determine that BLANCO possesses strengths that excel, mainly in the loyalty of the clients to cover the expectations of the users of the services that it offers, among the weaknesses the one that stands out more is the lack of marketing strategies for Promote their services. In the analysis of external factors, it was possible to show that "Aesthetics has all the respective permits for its normal operation, such as: operating permit granted by the Municipal GAD of Loja, and the RUC issued by the SRI. In establishing the annual operational plan, it was possible to determine the actions to be carried out, the execution period of each activity and the persons responsible for compliance. This annual plan also allowed the preparation of the budget of the marketing plan and establish a control guide of the activities. Once all the objectives of the marketing plan have been met, the relevant conclusions and recommendations are presented.